Effect of Cryopreservation on Biological Markers of Sperm Function and their Correlation in Different Dog Breeds (Global Journal of Medical Research, 2021)
In the present study, we compared motility, viability, plasma membrane integrity (PMI), acrosome integrity (AI), inner mitochondrial membrane potential (IMMP), ATP and LDHC in freshly extended (FE,) and frozen-thaw (FT) semen among the dogs and breeds. Freshly extended semen in Tris-citric acid-fructose-egg yolk plasma-glycerol extenderwas also subjected to in vitro capacitation and acrosome reaction. Pearson correlation coefficient among the sperm attributes of FE and FT semen has been evaluated.Sperm attributes in FE and FT semen vary significantly (P
Keywords: biological markers; correlation; cryopreservation; semen; dogs